2016
DOI: 10.1002/adfm.201604545
|View full text |Cite
|
Sign up to set email alerts
|

Designing Thin, Ultrastretchable Electronics with Stacked Circuits and Elastomeric Encapsulation Materials

Abstract: Many recently developed soft, skin-like electronics with high performance circuits and low modulus encapsulation materials can accommodate large bending, stretching, and twisting deformations. Their compliant mechanics also allows for intimate, nonintrusive integration to the curvilinear surfaces of soft biological tissues. By introducing a stacked circuit construct, the functional density of these systems can be greatly improved, yet their desirable mechanics may be compromised due to the increased overall th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 48 publications
0
36
0
Order By: Relevance
“…In this regard, programmable laser treatment can easily construct bridge–island‐structured devices ( Figure a), where the unstretchable GHEGs (islands) are directly connected by electric conductive serpentine rGO interconnect (bridges). The GHEGs will remain undeformed when stretched, while the serpentine rGO interconnect undergoes lateral buckling to accommodate the applied strain, transforming high tensile deformation into bending deformation on bridges and resulting in large strength deformation of final device . Finite‐element analysis (FEA) reveals that the highest tensile strain of the device with three serpentine interconnect units is only 0.89% (Figure a), which is much lower than the critical strain at break of GO film (Figure S19, Supporting Information) .…”
mentioning
confidence: 99%
“…In this regard, programmable laser treatment can easily construct bridge–island‐structured devices ( Figure a), where the unstretchable GHEGs (islands) are directly connected by electric conductive serpentine rGO interconnect (bridges). The GHEGs will remain undeformed when stretched, while the serpentine rGO interconnect undergoes lateral buckling to accommodate the applied strain, transforming high tensile deformation into bending deformation on bridges and resulting in large strength deformation of final device . Finite‐element analysis (FEA) reveals that the highest tensile strain of the device with three serpentine interconnect units is only 0.89% (Figure a), which is much lower than the critical strain at break of GO film (Figure S19, Supporting Information) .…”
mentioning
confidence: 99%
“…Previous studies have shown that buckling and postbuckling deformation of thin films can greatly improve the reversible stretchability of interconnects [15,19,20]. Because the critical buckling strain (which is proportional to the thickness squared) of such thin interconnects is small, out-of-plane deformation commencing upon buckling significantly reduces the strain energy in metal interconnects.…”
Section: Resultsmentioning
confidence: 99%
“…Because of this irreversible deformation, the life-cycle of the stretchable supercapacitor array is expected to be much shorter than what is desirable for stretchable electronics ( ∼ 1000 cycles). Based on a commonly used criterion in finite element analysis validated by cyclic mechanical testing and four-probe resistance measurements [19][20][21][22], i.e. the maximum principal strain exceeding the yield strain in half of the width of an interconnect section, it was found that the reversible uniaxial stretchability of this supercapacitor array is only 8%.…”
Section: Introductionmentioning
confidence: 99%
“…At present, integrating inorganic or organic electronic materials with elastomeric substrates is the major approach to fabricate stretchable conductors. However, complicated and expensive fabrication and limited stretchability hinder the application of inorganic electronic materials [11][12][13][14][15]. The organic electronic materials own good stretchability, but their conductivities are lower than those of metal materials [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%